Changes in depressive symptoms among family caregivers of patients with cancer after bereavement and their association with resilience: A prospective cohort study. Issue 1 (7th August 2021) - Shimizu, Yoichi; Hayashi, Akitoshi; Maeda, Isseki; Miura, Tomofumi; Inoue, Akira; Takano, Mayuko; Aoyama, Maho; Matsuoka, Yutaka J.; Morita, Tatsuya; Kizawa, Yoshiyuki; Tsuneto, Satoru; Shima, Yasuo; et al.
Abstract: Objectives: To elucidate changes in depressive symptoms after bereavement and the impact of pre‐loss resilience on such changes and on the extent of complicated grief and posttraumatic growth. Methods: Prospective cohort surveys were provided to family caregivers of patients with cancer in four palliative care units (PCUs) before and after bereavement. Pre‐loss Connor–Davidson Resilience Scale scores, pre‐ and post‐loss Patient Health Questionnaire‐9 scores, post‐loss Brief Grief Questionnaire scores, and the expanded Posttraumatic Growth Inventory scores were determined. Results: Out of 186 bereaved family caregivers, 71 (38.2%) responses were analyzed, among which 47% pre‐loss and 15% post‐loss responses suggested to be a high risk for major depressive disorder (MDD). Approximately 90% of family caregivers at a high risk for post‐loss MDD were already at a high risk for pre‐loss MDD. Even after adjustment of the background variables as covariates, the interaction effect between family caregivers' pre‐loss depressive symptoms and resilience on post‐loss depressive symptoms was observed ( F  = 7.29; p  < 0.01). Moreover, pre‐loss resilience was not associated with other bereavement outcome measures. Conclusions: Among family caregivers of patients with cancer in PCUs, 47% and 15% had high risk for MDD before and after bereavement, respectively. Moreover, pre‐loss resilience mitigated post‐loss depressive symptoms among family caregivers who had high risk for MDD before bereavement. However, considering the study's small sample size, further research is needed.